Circulating collagen breakdown products as a biomarker for presence and instability of human intracranial aneurysms - Hackenberg, Katharina; Richter, Peter; Hetjens, Svetlana; Dreier, Rita; Ratliff, Thomas; Akanji, Oluwadamilola; Dremel, Judith; Abdulazim, Amr Nabil; Al Masalemh, Ibrahim; Al-Zghloul, Mansour; Neumaier-Probst, Eva; Groden, Christoph; et al. (European stroke journal, 2024)
Introduction: There is an unmet need for improved detection of intracranial aneurysms (IAs) and distinction between stable and unstable (high rupture risk) IAs. Within the IA wall, synthesis and degradation of type I collagen as the main molecular constituent balance each other to maintain IA stability. We hypothesized that collagen breakdown products could serve as molecular markers for IA presence and instability. - Patients and methods: This prospective, cross-sectional, single-center study included patients with unstable (growing/symptomatic/ruptured) and stable IAs and controls. We determined C-telopeptide (CTx) and c-terminal telopeptide (ICTP) as breakdown products of type I collagen in arterial and venous blood. - Results: We included 107 participants with IAs (52 stable/44 unstable) and 41 controls. The correlation between intra-aneurysmal and venous levels was r = 0.63 (p < 0.001) for ICTP, r = 0.55 (p = 0.001) for CTx. The odds of harboring an IA were five times higher for participants with high compared to low venous levels of collagen breakdown products (ICTP: odds ratio (OR) 4.9 (95% CI 1.1-22.7); CTx: OR 5.3 (95% CI 1.4-20.0)). The OR for having an unstable IA was 9.3 (95% CI 2.1-41.5) for patients with high compared to low venous ICTP levels. The area under the curve for ICTP levels as a marker for IA instability was 0.75. - Discussion and conclusion: Increased levels of venous collagen breakdown products, especially ICTP levels, could serve as a biomarker for IA presence and instability and complement current data for management of unruptured IAs on an individual patient level. Future studies with longitudinal data are needed to validate ICTP as a biomarker for high risk IAs.
In der Vorlage ist der Name Al Masalemh fälschlich als Al Masalmeh angegeben
Gesehen am 31.03.2025